The death penalty: debating the moral, legal and political issues - Baird, Robert M.; Rosenbaum, Stuart E. (Prometheus Books, 2011)
"Does capital punishment act as a deterrent to the commission of certain crimes? Is state-sponsored execution of criminals abhorrent to the standards of civilized society? Should the death penalty be outlawed as a violation of the Eighth Amendment to the US Constitution, which prohibits cruel and unusual punishment? Should it be outlawed because of the possibility that an innocent person may be executed? Questions such as these are at the heart of the debate over capital punishment. In this excellent anthology, leading experts examines all sides of this thorny issue. Besides age-old questions surrounding the death penalty, some of the articles also address the impact of new advances in DNA technology. In addition, editors Baird and Rosenbaum provide edited excerpts from two recent, controversial decisions by the United States Supreme Court. In both cases, the Eighth Amendment came into play. In the first, Kennedy v. Louisiana, the Court ruled that the death penalty for raping a child, even in the case of violent rape, when the death of the child is not the result, constitutes cruel and unusual punishment. In the second, Baez v. Rees, the Court confirmed a lower court's decision that the method of capital punishment used in most states--lethal injection--does not violate the Eighth Amendment. Anyone seeking greater clarity on the moral, legal, and political implications of this often-emotional debate will benefit from this balanced collection"--Provided by publisher